2006
DOI: 10.1007/s00345-006-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour, sexual dysfunctions and related help seeking patterns in middle-aged and elderly Europeans: the global study of sexual attitudes and behaviors

Abstract: To study the sexual activity and the prevalence of sexual dysfunctions and related help seeking behaviour, among people in Europe aged 40-80 years. A telephone survey was carried out in 2001-2002 in Sweden, the UK, Belgium, Germany, Austria, France, Spain and Italy, of 4,977 men and 5,023 women, using a structured, standardized questionnaire Eighty-three percent of men and 66% of women had sexual intercourse during the year preceding the interview. The sexual dysfunctions most frequently reported were early ej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 27 publications
7
92
1
8
Order By: Relevance
“…In addition, studies have identified a decrease in sexual interest and activity in old age. 34,35 There are similar results indicating that as the age advanced; the anxiety over sexual problems caused by the disease diminishes in our study. For this reason, the anxieties of the elderly women who do not have fertility concern are focused on the problems in diagnosis and treatment process rather than sexual life.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, studies have identified a decrease in sexual interest and activity in old age. 34,35 There are similar results indicating that as the age advanced; the anxiety over sexual problems caused by the disease diminishes in our study. For this reason, the anxieties of the elderly women who do not have fertility concern are focused on the problems in diagnosis and treatment process rather than sexual life.…”
Section: Discussionsupporting
confidence: 86%
“…Tramadol is also known to help against PE [20], however none of the participant reported on using it. Although the self-reported psychosocial distress was perceived as high, the fraction of men with PE seeking professional information about PE was low similar to previous reports [21,22]. Only 10% consulted their family doctor and/or were referred to an urologist, similar to the 9% in the PEPA survey [3].…”
Section: Discussionsupporting
confidence: 82%
“…A variety of reasons may explain this low percentage, such as men do not have a family doctor, do not know that a physician can help and that medical treatment is available, feeling ashamed of talking about PE, do not consider PE a disease as was found in our survey, or expect little or no improvement as a result of seeking treatment [3]. Physicians should be encouraged to ask men about their sexuality and in particular about sexual dysfunctions or complaints, as proactive inquiry by a physician may be the most promising approach to engaging patients into a discussion about sexual difficulties [21][22][23]. We observed significant differences for coexisting overweight (21% vs 30%), depression (9% vs 14%) and ED (3% vs 15%) between men without PE and men with PE.…”
Section: Discussionmentioning
confidence: 89%
“…Sexual dysfunction is not only prevalent in couples of more advanced age (Lindau et al, 2007), but also middle-aged couples, which often are still pursuing fertility (Nicolosi et al, 2006). Male sexual dysfunction in infertile couples can sometimes be the reason for infertility, but is more often either caused or aggravated by the fact of infertility and its own psychological implications (Shindel et al, 2008a, b).…”
Section: Paternal Age and Sexual Functionmentioning
confidence: 99%